2009
DOI: 10.2134/jeq2008.0413
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification in Wood Chip Bioreactors at Different Water Flows

Abstract: Subsurface drainage in agricultural watersheds exports a large quantity of nitrate-nitrogen (NO(3)-N) and concentrations frequently exceed 10 mg L(-1). A laboratory column study was conducted to investigate the ability of a wood chip bioreactor to promote denitrification under mean water flow rates of 2.9, 6.6, 8.7 and 13.6 cm d(-1) which are representative of flows entering subsurface drainage tiles. Columns were packed with wood chips and inoculated with a small amount of oxidized till and incubated at 10 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
62
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 38 publications
(64 reference statements)
7
62
1
Order By: Relevance
“…8). Others have similarly noted increased N removal at higher retention times in both lab and field studies (Chun et al, 2009;Greenan et al, 2009;Woli et al, 2010;Christianson et al, 2012). Here, to meet a 45% reduction of N as recommended by the U.S. Environmental Protection Agency Science Advisory Board (USEPA, 2007), the original data would require a theoretical retention time of 27 h, and the modified models would require 15 and 8.5 h for the May 30 tracer (outlet only sampled) and May 17 tracer (all wells sampled) model corrections, respectively.…”
Section: Seasonal and Hydraulically Driven Performance Fluctuationsmentioning
confidence: 92%
“…8). Others have similarly noted increased N removal at higher retention times in both lab and field studies (Chun et al, 2009;Greenan et al, 2009;Woli et al, 2010;Christianson et al, 2012). Here, to meet a 45% reduction of N as recommended by the U.S. Environmental Protection Agency Science Advisory Board (USEPA, 2007), the original data would require a theoretical retention time of 27 h, and the modified models would require 15 and 8.5 h for the May 30 tracer (outlet only sampled) and May 17 tracer (all wells sampled) model corrections, respectively.…”
Section: Seasonal and Hydraulically Driven Performance Fluctuationsmentioning
confidence: 92%
“…A wide range of nitrate removal effectiveness (up to 98% nitrate reductions) in laboratory and field studies has been reported in the literature (Greenan et al, 2009;Chun et al, 2009Chun et al, , 2010Moorman et al, 2010;Verma et al, 2010;Woli et al, 2010;Christianson et al, 2012b;Bell et al, 2015). Most have been designed as plasticlined trenches, filled with mixed-species wood chips, that receive tile flow from fields ranging from 1 to 20 ha in size (e.g., Woli et al, 2010;Christianson et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…As nitrate (NO 3 -N) is highly soluble and mobile, excess NO 3 -N may be released to groundwater and surface waters, reducing water quality there (Ciarlo et al 2007;Kröger et al 2007;Gordon et al 2008;Greenan et al 2009;Seitzinger et al 2010;Chintala et al 2013). Denitrifying bioreactors within subsurface water pathways have proven to be effective tools for the mitigation of NO 3 -N loads in impacted groundwater or drainage water (Schipper et al 2010a;Christianson et al 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…Denitrifying bioreactors facilitate denitrification by supplying these bacteria with an additional carbon source in an oxygen-poor and nitrate-enriched environment (Schipper et al 2010a;Christianson et al 2012b). The efficiency of the NO 3 -N removal in bioreactors depends on the retention time (Chun et al 2009;Greenan et al 2009), the amount and quality of the organic carbon source (Robertson et al 2000;Schipper et al 2010a), the NO 3 -N concentration in the source water (Schipper et al 2005;Chun et al 2009), the temperature (Robertson et al 2000), and the pH (Rivett et al 2008). Infield subsurface bioreactors can reduce NO 3 -N concentrations by up to 100 % of the original loads and often maintain their removal efficiency over several years (Robertson et al 2000;Schipper et al 2010a;Woli et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation